The Repo Auctions of the European Central Bank and the Vanishing Quota Puzzle - Dieter Nautz; Jörg Oechssler (University of Bonn, Bonn Graduate School of Economics (BGSE), 2001)
Weekly repo auctions are the European Central Bank's most important policy instrument. Provided that banks bid seriously, these auctions should determine the liquidity of the banking sector in an efficient and transparent way. However, under the fixed rate tender procedure used until June 2000, banks increasingly overbid which eventually forced the ECB to switch to the variable rate tender format. This paper investigates the overbidding phenomenon from a theoretical and an empirical point of view. Our empirical results confirm the weakness of the fixed rate tender format and indicate that the ECB's liquidity management has significantly improved since the switch to the variable rate system.
Keywords: E25; D44; 330; Repo Auctions